Independent and Joint Associations Between Leisure Time Physical Activity and Strength Activities With Mortality Outcomes in Older Adults At least 65 Years of Age: A Prospective Cohort Study. (15th April 2021) - Nie, Jing; Haberstroh, Michelle; Acosta, Tania; Huang, Wentao; Wang, Yafeng; Barengo, Noël C
Abstract: Scientific evidence regarding the combined effect of both aerobic leisure-time physical activity (LTPA) and muscle-strengthening activities on all-cause, cardiovascular disease (CVD), or cancer mortality in older adults is scant. The aim of the study was to investigate the associations between recommended physical activity and mortality in adults 65 years or older. This prospective cohort study used data from the National Health Interview Surveys from 1997 to 2013 linked with mortality files through December 31, 2015 ( n = 89 962). The main outcomes included all-cause, CVD, and cancer mortality. The main exposure variables were aerobic LTPA and guideline-concordant strength training during leisure time. Cox regression models were used to calculate the hazard ratios (HRs) and the corresponding 95% confidence intervals (CIs). Muscle-strengthening activity at least twice per week were associated with lower hazards of all-cause mortality (HR 0.92; 95% CI 0.88–0.96), CVD mortality (HR 0.90; 95% CI 0.81–0.99), and cancer mortality (HR 0.87; 95% CI 0.79–0.96). Those who reached the recommended weekly amount of LTPA had a lower hazard of all-cause mortality by 35% (HR 0.66; 95% CI 0.63–0.67), the hazard of CVD by 38% (HR 0.62; 95% CI 0.58–0.67), and cancer mortality by 22% (HR 0.78; 95% CI 0.73–0.84). The hazard of death among those who were physically active in both leisure time and engaged in muscle-strengthening activities was 0.57 (95% CI 0.54–0.60) for all-cause mortality, 0.53 (95% CI 0.47–0.61) for CVD mortality, and 0.66 (95% CI 0.58–0.75) for cancer mortality. Thus, engaging in muscle-strengthening activity at least 2 times/week may provide additional benefits among physically active older adults.